2020
DOI: 10.31893/jabb.20010
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the injection of vitamins AD3E and the seasons on some blood traits, biochemical components and hormones of Arabi rams

Abstract: The objective of this study was to determine the effect of the injection of different levels of AD3E vitamins in improving the productivity and reproductive performance of the Arabi rams in different seasons. This study was conducted in the animal field of the College of Agriculture-University of Basrah, Karmat Ali, for the period from December 2017 to March 2018 (three months winter) and June 2018 until September 2018 (three months in summer). The study used 21 Arabi sheep with 2.5 years old and weights from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…The VAD3E group showed high ACH50, total Ig, and LZY values in this study. The vitamin AD3E mixture might stimulate the immune system by increasing immunoglobulin levels [26].…”
Section: Discussionmentioning
confidence: 99%
“…The VAD3E group showed high ACH50, total Ig, and LZY values in this study. The vitamin AD3E mixture might stimulate the immune system by increasing immunoglobulin levels [26].…”
Section: Discussionmentioning
confidence: 99%
“…The results of Table (5) showed that there were no significant differences in hemoglobin Hb values in the first month of the experiment, despite the presence of an arithmetic increase for T3 treatment, which recorded an average of (12.33) g/cm3, followed by treatment T2 with an average of (11.33) g/cm3 and treatment T1 The lowest average treatments were (10.67) g/cm3, while the significant increase appeared in the second and third months of the experiment for AD3E treatments (T3 and T1) compared to the T1 group.…”
Section: -2-2-(hb) Hemoglobin Concentrationmentioning
confidence: 99%
“…The primary function of ghrelin is to activate receptors primarily located in the brain's appetite center, signaling the body's nutritional status and energy requirements [6]. Research indicates that ghrelin plays a role in regulating fat distribution throughout the body [7] and facilitates fat absorption and storage in adipose tissue [8]. Additionally, this hormone is involved in stimulating the synthesis of growth hormone, prolactin, and adrenal cortex hormones to enhance food intake following a period of fasting [9].…”
Section: Introductionmentioning
confidence: 99%